PERAN DIREKTORAT RESERSE KRIMINAL KHUSUS (DITRESKRIMSUS) POLDA BALI DALAM MENYELESAIKAN KASUS TINDAK PIDANA PERETASAN - Ni Made Liana Dewi; Suastyayana, Komang Mas (Fakultas Hukum Universitas Dwijendra, 2026)
Hacking refers to an act carried out by someone who unlawfully breaches into another person's computer or computer network in any way, with the intention of obtaining certain data owned by the victim. The purpose of this research is to investigate the effectiveness of law enforcement against personal data hacking crimes by the Subdirectorate of Cyber Crime (Subdit Siber) of the Criminal Investigation Directorate (Ditreskrimsus) of the Bali Police, as well as the challenges faced in law enforcement against personal data hacking crimes by the same unit. The research method used in this study is empirical juridical. Empirical juridical research examines and analyzes the functioning of law in society (law in action), with primary data sourced from the field. The findings of this study indicate that law enforcement against personal data hacking crimes by the Subdit Siber Ditreskrimsus Bali has not been effective, as evidenced by the continued high rate of personal data hacking cases and the lack of public awareness and vigilance. The conclusion of this research is that the effectiveness of law enforcement against personal data hacking crimes by the Subdit Siber Ditreskrimsus Bali is not yet effective, largely due to the general public’s lack of awareness regarding the security of their social media accounts. The challenges in law enforcement against personal data hacking crimes by the Subdit Siber Ditreskrimsus Bali include the hijacking of bank account information and the hacking of social media accounts. A key challenge is that social media servers are located outside of Indonesia, which causes difficulties in coordination with social media platform providers, and perpetrators can hide their identities by altering their IP addresses.